2021
DOI: 10.1108/xjm-03-2021-0072
|View full text |Cite
|
Sign up to set email alerts
|

Something beyond paycheque to boosting employee retention: evidence from a South Indian hospital

Abstract: Purpose This paper aims to emphasize the need for a strategic approach to employee retention beyond financial benefits. This is directly proportional to employee retention. Bringing out the retention measures preferred by employees, depicting the relationship of demographic profile with employee retention tendency and exploring implications giving importance to beyond paycheque factors are the objectives of the study. Design/methodology/approach This study uses applied qualitative approach with a realistic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Such workplace attitudes form an integral part of successful performance and organizational effectiveness, especially in the healthcare sector (Afolabi et al ., 2018; Goldstein, 2003; Lambrou et al ., 2010; Mosadeghrad and Ferdosi, 2013; Ng et al ., 2021; Shantz et al ., 2016; Top et al ., 2015; Garg, 2020). Moreover, studies have indicated an intention to quit and turnover as severe issues in the healthcare sector (Bharath, 2021) and within the Indian cultural context (Dasgupta, 2015; Srinivasan and Chandwani, 2014; Garg, 2017). Together they are a clarion call to action for researchers, making the present examination of workplace toxicity, its impact on turnover intentions and ways for managing it highly relevant in this sector.…”
Section: Discussionmentioning
confidence: 99%
“…Such workplace attitudes form an integral part of successful performance and organizational effectiveness, especially in the healthcare sector (Afolabi et al ., 2018; Goldstein, 2003; Lambrou et al ., 2010; Mosadeghrad and Ferdosi, 2013; Ng et al ., 2021; Shantz et al ., 2016; Top et al ., 2015; Garg, 2020). Moreover, studies have indicated an intention to quit and turnover as severe issues in the healthcare sector (Bharath, 2021) and within the Indian cultural context (Dasgupta, 2015; Srinivasan and Chandwani, 2014; Garg, 2017). Together they are a clarion call to action for researchers, making the present examination of workplace toxicity, its impact on turnover intentions and ways for managing it highly relevant in this sector.…”
Section: Discussionmentioning
confidence: 99%
“…Employee retention is also defined as strategies or practices that contribute to keeping employees longer in organizations (Islam et al, 2022). For employee retention management to be effective, it is not only important to create optimal human resource practices but also to manage employees' perceptions regarding what their organization has promised them in return for their loyalty and commitment (Bharath, 2023;Fahim, 2018). This implies that retention practices might be successful only if they are consistent with the value of employees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can lead to increased loyalty and retention rates as employees feel that their financial needs are being met (Dwomoh & Frempong, 2017). Compensation can also be a powerful motivator for employees (Bharath, 2023). When employees are fairly compensated and have access to performance-based incentives, they are more likely to be motivated to perform at their best.…”
Section: Compensationmentioning
confidence: 99%
“…Poor leadership styles, long working hours, inadequate salaries, inconsistent work environments, and ill-de ned job descriptions contribute to a high nurse turnover due to degraded nursing experiences 14 . These turnovers result in patient dissatisfaction, compromised patient safety, and a decline in the reputation of healthcare institutions 15 .…”
Section: Nursing Sector Challenges In Indiamentioning
confidence: 99%